Association Between Alcohol Consumption and Blood Pressure Levels Among HIV Sero-Positive and Sero-Negative Cohorts: A Secondary Analysis of the Vukuzazzi Study - Manasseh B. Wireko; Jacobus Hendricks; Kweku Bedu-Addo; Marlise Van Staden; Emmanuel A. Ntim; John A. Larbi; Isaac K. Owusu (SAGE Publishing, 2024)
Background: The effect of hypertension is aggravated by lifestyle factors such as alcohol consumption. This study sought to determine the association between alcohol consumption and the level of blood pressures among HIV seronegative and seropositive cohorts. Methods: This secondary analysis was performed on a cross-sectional survey data of 17 922 participants during the period between 2018 and 2020. A questionnaire was used to obtain participants' alcohol consumption history, which was categorized into non-alcohol consumers, non-heavy alcohol consumers, and heavy alcohol consumers. A linear regression model was used to establish relationships among participants with raised blood pressure (BP ≥ 140/90 mmHg). Results: Out of the total participants, 3553 (19.82%) were hypertensives. Almost 13% of the hypertensives (n = 458; 12.89%) were undiagnosed, and 12.44 % (442) had uncontrolled hypertension. About 14.52% of the hypertensives (3553) were not on any antihypertensive medication. Male non-consumers of alcohol had the highest systolic and diastolic BP; uncontrolled systolic BP (165.53 ± 20.87 mmHg), uncontrolled diastolic BP (102.28 ± 19.21mmHg). Adjusted for covariates, moderate alcohol consumption was associated with HTN among participants who were HIV seropositive [unadjusted (RR = 1.772, P  = .006, 95% CI (1.178-2.665)], [RR = 1.772, P  = .005, 95% CI (1.187-2.64)]. [unadjusted RR = 1.876, P  = .036, 95% CI (1.043-3.378)], adjusted RR = 1.876, P  = .041, 95% CI (1.024-3.437). Both moderate and heavy alcohol consumption were significantly related to hypertension among HIV sero-negative [unadjusted model, moderate consumption RR = 1.534 P  = .003, 95% CI (1.152-2.044)], [adjusted model, moderate alcohol consumption RR = 1.535, P  = .006, 95% CI (1.132-2.080)], [unadjusted model, heavy alcohol consumption, RR = 2.480, P  = .030, 95% CI (1.091-5.638)], [adjusted model RR = 2.480, P  = .034, 95% CI (1.072-5.738)]. Conclusion: Alcohol consumption is significantly related to increase BP regardless of HIV infection.